Joint equilibrium strategy for I/Q imbalance and CFO in MIMO OFDM system based on STBC - Hai-jun ZHAO; Min LI; Meng-tian CUI; Ming-dong LI (Tongxin xuebao)
Based on the STBC scheme, the combined effect of the transmitter and receiver I/Q imbalance, the front-end filter unmatch, CFO and frequency selective channel distortion for the presence at the same time in MIMO OFDM com-munication system was intensively studied , and an applicable joint equilibrium strategy was also proposed.The concrete implementation is that a frequency domain equalizer was firstly obtained through the analysis of the only presence of the transmitter I/Q imbalance and multipath channel interference in MI OFDM system. And then considering on the si-multaneous presence of receiver I/Q imbalance and CFO, two time domain equalizers were also obtained. Finally, these time domain equalizers were transformed into the frequency domain, combined with frequency domain equilibrium technology to eliminate the transmitter I/Q imbalance multipath channel interference. A comprehensively joint equi-librium technology, namely frequency domain per-tone equalizer, was proposed. The simulation results show that the frequency domain per-tone equilibrium technique for the proposed MIMO OFDM system can be extended to other higher order STBC system, and the BER performance of the system after equilibrium using the osed equilibrium technique is improved obviously.